2015
DOI: 10.1109/tst.2015.7297749
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches for prioritizing candidate disease genes based on PPI networks

Abstract: With the continuing development and improvement of genome-wide techniques, a great number of candidate genes are discovered. How to identify the most likely disease genes among a large number of candidates becomes a fundamental challenge in human health. A common view is that genes related to a specific or similar disease tend to reside in the same neighbourhood of biomolecular networks. Recently, based on such observations, many methods have been developed to tackle this challenge. In this review, we firstly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 102 publications
0
35
0
Order By: Relevance
“…The findings from the STRING, Cytoscape, GO, and KEGG analyses indicated that many pathways were primarily affected in OC. Several studies have used Cytoscape plugins such as MCODE, cytoHubba, CytoCluster, CytoKegg, and CytoNCA to elucidate the core interactions in PPI networks (Lan et al, 2015;Villaveces et al, 2015;Sriroopreddy and Sudandiradoss, 2018;Zhang et al, 2019). To delineate the molecular interactions and pathways identified from the STRING, GO, and KEGG analyses, we utilized GeneGo Metacore, which has a massive amount of information about regulatory and metabolic pathways and contains precisely curated biological networks.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the STRING, Cytoscape, GO, and KEGG analyses indicated that many pathways were primarily affected in OC. Several studies have used Cytoscape plugins such as MCODE, cytoHubba, CytoCluster, CytoKegg, and CytoNCA to elucidate the core interactions in PPI networks (Lan et al, 2015;Villaveces et al, 2015;Sriroopreddy and Sudandiradoss, 2018;Zhang et al, 2019). To delineate the molecular interactions and pathways identified from the STRING, GO, and KEGG analyses, we utilized GeneGo Metacore, which has a massive amount of information about regulatory and metabolic pathways and contains precisely curated biological networks.…”
Section: Discussionmentioning
confidence: 99%
“…The Gene ontology (GO) information is useful for evaluating gene function similarity [36,37]. In here, we obtain GO data from Gene Ontology Consortium [38].…”
Section: Data Preparationmentioning
confidence: 99%
“…ATG genes have been used in supervised machine learning models applied to ageing research [16] and are among the top features in models for predicting lifespan-extending chemicals [17]. Numerous studies have used machine learning (ML) methods to infer gene-disease associations [18][19][20][21]. However, the use of ML models to guide further autophagy research has not been previously discussed.…”
Section: Introductionmentioning
confidence: 99%